Dr. Jekyll and Mr. Hyde - Robertson, John S., 1878-1964; Barrymore, John, 1882-1942; Lane, Charles, 1869-1945; Stevenson, Robert Louis, 1850-1894.; Paramount Famous Lasky Corporation; Cinetel Films ([New York, NY] : Famous Players-Lasky Corporation, 1920)
A London doctor finds a drug that allows him to separate the evil side of his personality from the good.
Originally distributed by Paramount Pictures.
Based on the novella: The strange case of Dr. Jekyll and Mr. Hyde / by Robert Louis Stevenson.
John Barrymore, Charles Lane, Brandon Hurst, Cecil Clovelly, Nita Naldi, Alma Aiken, J. Malcolm Dunn, Martha Mansfield, George Stevens, Edgard Varèse, Louis Wolheim.
Photographed by Roy Overbaugh ; musical score compiled by Rodney Sauer ; performed by the Mont Alto Motion Picture Orchestra ; art directors, Robert M. Haas, Charles O. Seessel.
Silent, with English intertitles and musical accompaniment; optional Spanish subtitles.
Online resource; title from opening/closing credits (Digitalia Film Library, viewed August 14, 2015)
Keywords: Multiple personality -- Drama; Self-experimentation in medicine -- Drama; Feature films; Silent films; Horror films; Fiction films; Internet videos; Streaming video